GLUTEN PRODUCTION : ANALYSED IN TERMS OF VOLUME EXPANSION, EXTENSIBILITY AND RHEOLOGICAL CHARACTERISATION - Rihayat, Teuku; Helvina, Puteri (Politeknik Negeri Lhokseumawe, 2024)
ABSTRACT Gluten is the protein in flour that gives the viscoelastic properties of dough. There are still inadequate understandings of the knowledge concerning gluten during the dough mixing and the unique properties that gluten posses. Gluten production was examined in terms of quantity and quality of gluten. Quantity of gluten was measured in terms of wet and dry gluten content. Wet gluten content was determined by weighing the gluten obtained from the dough washed under running tap water. The wet gluten was dried using air oven drying method to obtain dry gluten content. In terms of quality, the gluten was analysed in terms of volume expansion, extensibility and rheological characterisation. The volume expansion analysis was performed by frying the wet gluten in hot oil at 170oC in deep fryer for 15 minutes. The volume of fried gluten was measured using mustard seed displacement method and the difference between the volume of fried gluten and the volume of wet gluten is measured as volume expansion of gluten.Keywords : Gluten, rheological, wheat